The Case of Holywings Bar and Its Existence Upon the Legal and Socio-Political Perspectives in Indonesia - Widjaja, Gunawan; Towpek, Hadenan (ARISTO, 2023)
The case of Holywings Bar is an issue that has garnered public attention following their social media promotions on alcoholic beverage products by including the names of Muhammad and Maria. This case is considered as a sensitive issue in a country with the majority of its population are Muslims. Thus, by the initiative of several community groups, this issue has been reported to the legal apparatus to stop all its operations in Jakarta and other big cities entirely. Based on the issue, this study is conducted to obtain a profound understanding toward the case of Holywings bar and its existence in Indonesia viewed from the legal and socio-political aspects. In discussing the problem of this study, we collect information from various newspapers and other legal and socio-political science publishers as the supporting data. Then, we analyze the datathrough phenomenological approach and draw conclusions believedas the best answer for the problem. Finally, the researchers conclude that the case of Holywings Bar is declared as having violated the law and business licensing regulations for bars that sell alcoholic beverages. According to several experts, the closure of Holywings Bar can be viewed from the legal and socio-political perspectivesrelated to the 2024 presidential election, since the majority of voters for presidential candidates are from Islamic groups who support the closure, and they are closely related to one of the presidential candidates in 2024. Hence, the results of this study are expected to be beneficial toward the development of similar studies in the future.